Heat transfer enhancement of magnetized nanofluid flow due to a stretchable rotating disk with variable thermophysical properties effects - Olayemi, Olalekan Adebayo; Obalalu, Adebowale Martins; Odetunde, Christopher Bode; Ajala, Olusegun Adebayo (Springer, 2022)
Ferrofluid is a one-of-a-kind substance that functions both as a magnetic solid and as a liquid. In this article, water-based Fe3O4 and Mn–ZnFe2O4 nanofluids between parallel stretchable spinning discs are considered. To carry out the study, the influence of rotational viscosity in the flow, which is due to the difference in rotation between the fluid and magnetic particles, and the applied magnetic field are examined. Additional impacts incorporated to the novelty of the model are the variable viscosity and variable thermal conductivity. The Legendre-based collocation method is used to solve the set of governing equations. To ensure the code validity, a comparison with analytical results is conducted and an excellent consensus is accomplished. Comparisons of the pertinent parameters on the flow profiles are displayed in tabular and graphical forms. Analyses reveal that the ferromagnetic Fe3O4 nanofluid shows higher thermal conductivity strength than the ferromagnetic Mn–ZnFe2O4 nanoparticles. This study finds its usefulness in aerospace, biotechnology, medical sciences, material sciences, and so on.